Slowly absorbable mesh versus standard care in the management of contaminated midline incisional hernia (COMpACT-BIO): a multicentre randomised controlled phase III trial including a health economic evaluation. Issue 8 (25th August 2022) - Passot, Guillaume; Margier, Jennifer; Kefleyesus, Amaniel; Rousset, Pascal; Ortega-Deballon, Pablo; Renard, Yohann; Bin, Sylvie; Villeneuve, Laurent
Abstract : Introduction: Incisional hernia (IH) is the most frequent mid-term and long-term complication after midline laparotomy. The current standard treatment includes repair using a mesh. In a contaminated field, the use of a non-absorbable mesh increases the risk of surgical site infection and the costs. Slowly absorbable meshes are safe in contaminated fields, but no data have been reported regarding their long-term recurrence rate. COMpACT-BIO is a multicentre prospective randomised controlled phase III trial designed to compare the 3-year recurrence rate in patients undergoing contaminated IH repair with either a slowly absorbable mesh or standard care. Methods: In patients undergoing midline IH repair in a contaminated surgical field (grade III of the modified Ventral Hernia Working Group classification), the COMpACT-BIO study compares the use of a slowly absorbable mesh with that of conventional care according to standardised surgical procedures (primary closure, non-absorbable synthetic mesh or biologic mesh, at the discretion of the surgeon). Randomisation is done during surgery before closure the fascia with an allocation ratio of 1:1. The choice of the slowly absorbable mesh is left to the criteria of each centre. The primary endpoint is the proportion of patients with scan-confirmed IH recurrence within 3 years after repair. Ethics/dissemination: This trial is conducted in compliance with international standards for research practice and reporting. Written informed consent will be obtained from patients prior to inclusion. All data were identified and anonymised prior to analysis. The protocol has been approved by an Institutional Review Board (2020-A0823-36/SI:20.07.03.66831), and will be conducted in compliance with the CONSORT (Consolidated Standards of Reporting Trials) statement. Results will be submitted for publication in peer-reviewed medical journals and presented to patients and healthcare professionals. Protocol version: Version 2—13 October 2020. Trial registration number: NCT04597840 .